Economic evaluation of the Midwifery Initiated Oral Health-Dental Service programme in Australia. Issue 8 (2nd August 2021) - Tannous, Kathy W; George, Ajesh; Ahmed, Moin Uddin; Blinkhorn, Anthony; Dahlen, Hannah G; Skinner, John; Ajwani, Shilpi; Bhole, Sameer; Yaacoub, Albert; Srinivas, Ravi; Johnson, Maree
Abstract : Objectives: To critically evaluate the cost-effectiveness of the Midwifery Initiated Oral Health-Dental Service (MIOH-DS) designed to improve oral health of pregnant Australian women. Previous efficacy and process evaluations of MIOH-DS showed positive outcomes and improvements across various measures. Design and setting: The evaluation used a cost-utility model based on the initial study design of the MIOH-DS trial in Sydney, Australia from the perspective of public healthcare provider for a duration of 3 months to 4 years. Participants: Data were sourced from pregnant women (n=638), midwives (n=17) and dentists (n=3) involved in the MIOH trial and long-term follow-up. Cost measures: Data included in analysis were the cost of the time required by midwives and dentists to deliver the intervention and the cost of dental treatment provided. Costs were measured using data on utilisation and unit price of intervention components and obtained from a micro-costing approach. Outcome measures: Utility was measured as the number of Disability Adjusted Life Years (DALYs) from health-benefit components of the intervention. Three cost-effectiveness analyses were undertaken using different comparators, thresholds and time scenarios. Results: Compared with current practice, midwives only intervention meets the Australian threshold (A50 000) of being cost-effective. The midwives and accessible/affordable dentists joint intervention was only 'cost-effective' in 6 months or beyond scenarios. When the midwife only intervention is the comparator, the midwife/dentist programme was 'cost-effective' in all scenarios except at 3 months scenario. Conclusions: The midwives' only intervention providing oral health education, assessment and referral to existing dental services was cost-effective, and represents a low cost intervention. Midwives' and dentists' combined interventions were cost-effective when the benefits were considered over longer periods. The findings highlight short and long term economic benefits of the programme and support the need for policymakers to consider adding an oral health component into antenatal care Australia wide. Trial registration number: ACTRN12612001271897; Post-results.